«It can be hidden from us, but not from God». Narratives of religious conversion in church pavilions leaders and production of the prison order in Argentina - Manchado, Mauricio (Universidad Nacional del Litoral, 2021)
The proposal of this article is to describe the dynamics that the Pentecostal Evangelical Religious Device (PERD) assumes in the construction of the prison order of Argentine prisons, based on the analysis of the narratives of religious leaders —named as servants— of the so-called «church pavilions». The narratives will be approached from two of its constitutive dimensions. On the one hand, the spiritual worldviews that compose them and on the other hand, their pedagogical dimension. Our hypothesis is that the intersection of both builds a narrative that promotes redemption scripts where two seemingly contradictory meanings prevail, although complementary to prison everyday life: salvation in individual terms, and redemption as a collective contribution to other members of the locked community. This intersection allows us to understand how a set of heterogeneous elements are articulated in the PERD, contributing to the daily management of the confinement. Analysis resulting from field work carried out for more than seven years in four prisons in the province of Santa Fe (Argentina), built from a qualitative approach and empirically based on participant observations and in-depth interviews with prisioners from the self-styled «Christian» wards or «churches», Directors and prison guards committed to the custody of those spaces.